2000
DOI: 10.1002/(sici)1097-0320(20000215)42:1<11::aid-cyto3>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets and specific T-cell immune response in thalassemia

Abstract: Infection is very common in thalassemia and is one of the major causes of death. To date, it is not quite clear why these patients are susceptible to infection. In this study, lymphocyte immunophenotyping for CD3 (T-cells), CD3 CD4 (T-helper/inducer cells), CD3 CD8 (T-suppressor/cytotoxic cells), CD3 CD19 (B-cells), and CD3 CD16/56 (natural killer cells) subsets and expression of the activation antigen CD69 on CD3 CD4 and CD3 CD8 T-cells were determined in the whole blood of thalassemia patients, using a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
6
8
1
1
Order By: Relevance
“…Difference in splenectomized patients percentages in these studies compared to the current study might be an explanation of the differences in B-lymphocyte results. Nevertheless, immunoglobulin results were consistent with the previous studies [5,[22][23][24].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Difference in splenectomized patients percentages in these studies compared to the current study might be an explanation of the differences in B-lymphocyte results. Nevertheless, immunoglobulin results were consistent with the previous studies [5,[22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…Contradictory results were reported in the literature for B cells in thalassemic patients. Our findings of normal B lymphocytes were in agreement with the study reported by Musumeci et al [22], but not consistent with the findings reported by Dwyer et al [5] and Pattanapanyasat et al [23]. A significant increase in CD19 + B cells was shown, particularly in splenectomized ones, and the mechanism suggested for increased CD19 + B cells in these studies was redistribution of B lymphocytes from the spleen to the circulating pool.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Different subsets of lymphocytes, including helper T cells, suppressor T cells, NKCs, and B cells (distinguished by respective phenotypic signatures of CD3+/CD4+, CD3+/CD8+, CD3-/CD16/56+, and CD3-/CD19+) have been reported with increased number in TM patients (21,22). Excess iron may exert executive effects on the ratio of T cell subsets, which may be reflected by increased number of CD8+ lymphocyte while decreased CD4+ subset (23).…”
Section: Quantitative Alternationsmentioning
confidence: 99%